A Case of Invasive Fungal Infection Of Optic Nerve - Shyam Kumar Gupta; Taru Dewan; Arun Kumar Patidar (Delhi Journal of Ophthalmology)
Neural spread is a rare mode of spread for fungal infection. We hereby report a case of a 55-year-old diabetic woman with intraneural invasion by Aspergillus. In this case blackish discolouration of the optic nerve head due to intraneural invasion and black growth in the lumen of retinal vessels due to intravascular spread was documented. This is the first fundus documentation of such a fungal growth in a living person.